Analisis Permasalahan dan Solusi Pembelajaran Bahada Indonesia di Sekolah Dasar dalam Meningkatkan Literasi Siswa - Nara Apriani; Nia Oktaviani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Literacy is a fundamental competency that needs to be developed starting at the elementary school level, as it plays a crucial role in students' ability to acquire, comprehend, process, evaluate, and communicate information. Indonesian language instruction plays a strategic role in enhancing literacy skills by fostering listening, speaking, reading, viewing, and writing abilities. However, the implementation of Indonesian language instruction in elementary schools still faces various challenges, such as low student interest in reading, limited use of instructional media, disparities in literacy levels among students, and suboptimal parental support in fostering a literacy culture at home. This study aims to analyze the challenges associated with Indonesian language instruction and describe the solutions implemented by teachers to improve student literacy at SDN 11 Sitiung. The study employs a qualitative approach with a descriptive design. The research subjects consisted of classroom teachers (as primary informants) and students (as secondary informants), selected through purposive sampling. Data were collected via observation, interviews, and documentation, and subsequently analyzed using the Miles, Huberman, and Saldaña model, involving stages of data condensation, data display, and conclusion drawing and verification. Data validity was ensured through source and technique triangulation. The results indicate that the challenges in Indonesian language instruction regarding student literacy improvement are influenced by both internal and external factors. Internal factors include low reading interest and varying literacy abilities among students, while external factors include limited use of instructional media and suboptimal family support. Solutions implemented by teachers include establishing a habit of reading prior to lessons, utilizing diverse instructional media, applying student-centered learning approaches, providing motivation, and strengthening collaboration with parents. These efforts contributed to increased student engagement in literacy activities, improved reading comprehension, and greater confidence in expressing opinions. Thus, enhancing student literacy within Indonesian language instruction requires appropriate teaching strategies and sustained collaboration among the school, the family, and the learning environment.